Parental Involvement in Adolescents' Healthy Eating Through Karuni Application: A Community Study in Indonesia - Baiquni, Fahmi; Hersipa, Lulung Lanova; Karuniawati, Benny; Novera, Milya; Wahid, Abdul; Safaringga, Miranie (UNIVERSITAS ALIFAH PADANG, 2025)
Background: Female adolescents in Indonesia frequently skip breakfast and have tea after meals, which leads to iron deficiency anemia. However, only a few interventions have successfully combined parental involvement and technology to promote healthy eating.Objective: Our hypothesis was that parents' facilitation through the KARUNI mobile app would lead to healthy eating habits in adolescent girls.Methods: The mixed-methods study recruited 108 female adolescents aged 12-15 years from Gunungkidul, Indonesia (58 intervention, 50 control). The intervention group was instructed to use KARUNI for 21 days with parental involvement, followed by focus group discussions and interviews.Results: In the intervention group, the frequency of breakfast consumption significantly increased (p<0.001) and tea/coffee intake after meals was significantly reduced (p=0.001) with large effect sizes (r>0.48). KARUNI was instrumental in enhancing parental nutrition knowledge, increasing adolescents' self-efficacy, and facilitating better health communication within the family.Conclusion: The engagement of parents through KARUNI resulted in a significant improvement in the adolescents' eating behaviors, indicating that family-centered and technology-enabled interventions can effectively tackle nutritional deficiencies in resource-poor environments.